# How do you get 24 from 9, 6, 11 and 3?

Fundamental operations are the basics of mathematics. These include addition, subtraction, multiplication and division.

## Answer: (11 - 6) × 3 + 9 = 24 or [(11 - 9) + 6] × 3 = 24

There can be two solutions to this question. Let's have a look at the explanation.

**Explanation:**

We use the fundamental operations on the numbers to obtain the given result 24.

i) First, we subtract 6 from 11. Then, we multiply the result by 3 and then add 9 to obtain the final result.

⇒ 11 - 6 = 5

⇒ (11 - 6) × 3 = 15

⇒ (11 - 6) × 3 + 9 = 24

ii) First, we subtract 9 from 11. Then we add 6 to the result. Then, we multiply the result by 3.

⇒ 11 - 9 = 2

⇒ (11 - 9) + 6 = 8

⇒ [(11 - 9) + 6] × 3 = 24

Hence, two solution are possible: (11 - 6) × 3 + 9 = 24 or [(11 - 9) + 6] × 3 = 24.